2010
DOI: 10.1590/s0034-737x2010000600009
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of propofol and thiopental on tear production in dogs

Abstract: RESUMO Comparação da produção lacrimal em cães após indução anestésica com Propofol e TiopentalO filme lacrimal tem função importante na manutenção da integridade da superfície ocular. Durante a anestesia geral sua produção é diminuída consideravelmente, o que exige cuidados para prevenir efeitos adversos que resultam em doenças destas estruturas. Ainda não foram realizadas pesquisas comparando-se os efeitos da indução com o tiopental e com o propofol na produção lacrimal. Como estas drogas são utilizadas na M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
0
9
0
2
Order By: Relevance
“…Differences found between the left and right eyes can be attributed to increased exposure of the ocular surface of the eye right to pachymetry, with subsequent drying, Pontes et al (2010) also observed differences in tear production between the eyes due to the greater exposure of the ocular surface of one of them.…”
Section: G3mentioning
confidence: 95%
See 2 more Smart Citations
“…Differences found between the left and right eyes can be attributed to increased exposure of the ocular surface of the eye right to pachymetry, with subsequent drying, Pontes et al (2010) also observed differences in tear production between the eyes due to the greater exposure of the ocular surface of one of them.…”
Section: G3mentioning
confidence: 95%
“…During this time, the eyelids of the eye examined remained closed. Then, the same procedure was performed on the left eye (STT-LE), using a new sterile strip (Slatter, 2005c;Pontes et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main cause is the suppression of parasympathetic innervation of the lacrimal gland, as demonstrated in rats and rabbits experimentally para-sympathectomized by sectioning of the greater superficial petrosal nerve [ 9 , 10 , 11 ]. A marked decrease in tear production after induction of anesthesia has been reported in humans [ 12 , 13 , 14 , 15 ] and in dogs, using different anesthetic and sedative protocols [ 16 , 17 , 18 , 19 , 20 , 21 ]. The loss of corneal integrity resulting from perioperative dry eye can lead to corneal abrasions, which are the most common ocular complication in humans during general anesthesia for non-ophthalmic surgery [ 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…, Pontes et al . ), and the decrease in tear production can be transient or irreversible. In human medicine, β‐blockers are recognised as reducing tear production when used either locally or systemically (Petounis & Akritopoulos ).…”
Section: Introductionmentioning
confidence: 99%